2021
DOI: 10.17796/1053-4625-45.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Pathogenic Microorganisms in Removable Orthodontic Appliances and Oral Mucosa in Children

Abstract: Objective: The aim of this study was to evaluate the frequency of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida species in removable orthodontic appliances (ROA) and the support oral mucosa in children. Study design: The study participants comprised 55 patients aged 6–12 years requiring ROA. The samples of biofilm colonization from the support oral mucosa and the ROA were taken prior to the use of the ROA (T0) and 4 weeks (T1) after ROA placement. The biofilm samples were seeded on chromogenic cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…This was confirmed by the salivary results (p < 0.001) of Arab et al 8 and by a plaque analysis (p < 0.05) conducted by Shukla et al 22 Zheng et al 21 also reported a significant increase of Candida counts (p < 0.001) in gargled samples, finding a higher (p < 0.05) percentage of Candida carriers after 2 months of FOA, compared to pre-treatment. Different results were reported by Lee et al 16 and Grzegocka et al, 23 who determined a non-significant increase of Candida, after analysing saliva samples. In addition, Soler et al 24 found no significant differences at the vestibular level, while Kouvelis et al 27 reported that Candida was not identified in any sample before and after 4 weeks of FOA.…”
Section: Short-term (<3 Months) Candida Changesmentioning
confidence: 59%
See 2 more Smart Citations
“…This was confirmed by the salivary results (p < 0.001) of Arab et al 8 and by a plaque analysis (p < 0.05) conducted by Shukla et al 22 Zheng et al 21 also reported a significant increase of Candida counts (p < 0.001) in gargled samples, finding a higher (p < 0.05) percentage of Candida carriers after 2 months of FOA, compared to pre-treatment. Different results were reported by Lee et al 16 and Grzegocka et al, 23 who determined a non-significant increase of Candida, after analysing saliva samples. In addition, Soler et al 24 found no significant differences at the vestibular level, while Kouvelis et al 27 reported that Candida was not identified in any sample before and after 4 weeks of FOA.…”
Section: Short-term (<3 Months) Candida Changesmentioning
confidence: 59%
“…Of the 16 included studies, all were prospective in nature and included four reports which described the changes in Candida in patients treated using a ROA 13,17,20,26 and nine studies which described those treated with FOA. 8,[14][15][16][21][22][23][24]27 Three studies analysed and compared treated and non-treated patients, two of which involved a ROA 17,18 and one used FOA 25 . An additional untreated group served as a control.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa (P. aeruginosa), Staphylococcus aureus (S. aureus) and Candida albicans (C. albicans) are opportunistic pathogens responsible of different clinical conditions involving the oral cavity [9]. Due to their strong ability to adhere and persist on abiotic and biotic surfaces, they often cause biofilm-associated infections, which are clinically relevant and difficult-to-treat [10].…”
Section: Introductionmentioning
confidence: 99%
“…[14]. Recently, Rodriguez-Renteria et al [15] investigated after 4 weeks the frequency of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida species on removable orthodontic appliances and found that, of the 55 removable orthodontic appliances studies, Staphylococcus aureus was present on 90.9%, Pseudomonas aeruginosa on 67.7% and Candida species on 32.7% of the appliances. Interestingly, these microorganisms were also found in the support oral mucosa of the 55 children (respectively 89.09%; 60%; 30.9%).…”
Section: Introductionmentioning
confidence: 99%